Phase separated behavior in yttrium doped CaMnO3. (May 2016) - Sharma, Neetika; Das, A.; Prajapat, C.L.; Kumar, Amit; Singh, M.R.
Graphical abstract: Highlights: Electron doped manganite. Magnetic phase separation observed. Structural transition coupled with magnetic transition. Abstract: The effect of electron doping on the structural, transport, and magnetic properties of Mn (IV)—rich Ca1−x Yx MnO3 (x ≤ 0.2) samples have been investigated using neutron diffraction, neutron depolarization, magnetization and resistivity techniques. The temperature dependence of resistivity follows the small polaron model and the activation energy exhibits a minimum for x = 0.1 sample. A phase separated magnetic ground state consisting of ferromagnetic domains (∼7 μm) embedded in G-type antiferromagnetic matrix is observed in the sample, x = 0.1. The transition to the long-range magnetically ordered state in this sample is preceded by a Griffith's phase. On lowering temperature below 300 K a structural transition from orthorhombic structure ( Pnma ) to a monoclinic structure ( P21 /m ) is observed in the case of x = 0.2 sample. The ferromagnetic behavior in this case is suppressed and the antiferromagnetic ordering is described by coexisting C-type and G-type magnetic structures corresponding to the monoclinic and orthorhombic phases, respectively.